OP71 Understanding Hospitals' Performance Variability: Conceptual Framework. (2019) - Cicchetti, Americo; Marchetti, Marco; Gabutti, Irene; Boccia, Stefania; Specchia, Maria Lucia; Biondi, Alessia; Ceccarelli, Anna; de Waure, Chiara; Grossi, Adriano; Hoxhaj, Ilda; Cacciatore, Pasquale; Carini, Elettra; et al.
Abstract : Introduction: Understanding of the role of contextual factors in determining the real value of health technologies is one of the major challenges for the use of Health Technology Assessment (HTA) methodology within hospitals. Moreover, the responsibility of assessing hospital performance is problematic. Although a number of managerial tools are available to appraise outcomes, there is little evidence on the role of contextual variables and how they might contribute to hospital performance. Methods: Based on three extensive literature reviews, a pragmatic framework has been developed to understand interactions between organizational factors and health technologies on hospitals' performance. Three main causal relationships emerge: (i) direct relationship between contextual factors and performance; (ii) an effect of contextual factors on the capability of technologies to "produce value"; (iii) an influence of organizational factors on clinical evidence-based decision-making. This pragmatic framework was designed within the IMPACT HTA EU Horizon 2020 Research Project. Results: The contextual dimensions are ascribable to five domains: organizational structure; managerial accounting tools; information, communication and technology (ICT) tools; human resource management (HRM) tools; hospital-based HTA procedures. The impact of contextual factors on technologies' ability to produce value is highly overlooked in literature. Some effort in this sense exists only in the analysis of health information technologies. Moreover, among the contextual dimensions, only HRM tools have inspired a lively debate. The definition of hospital performance is amenable to multiple domains: accessibility, appropriateness, efficiency, safety and patient centeredness (continuity of care). Conclusions: Although hospital performance is a pivotal topic in the healthcare sector, a deep understanding of how contextual factors may affect it is missing. The theoretical framework developed provides a tool to understand the multiple dimensions able to affect hospital performance. On one hand contextual dimensions may provide a direct effect on hospital performance. On the other, they may affect the extent to which technologies are capable of producing value.